PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - rahayu, siti sarah Santika (COMPETITIVE, 2023)
This study aims to determine 1) The effect of the audit committee on firm value in food and baverage companies listed on the IDX for the 2016-2019 period 2) The effect of managerial ownership on firm value in food and baverage companies listed on the IDX for the 2016-2019 period 3) The effect of board independence commissioners on the value of companies in food and baverage companies listed on the IDX for the period 2016-2019. 4) The influence of Corporate Social Responsibility on the value of companies in food and baverage companies listed on the IDX for the period 2016-2019. The method used is quantitative data and associative approach. The sampling technique used was purposive sampling technique. The data analysis technique used Descriptive Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing, F Test and R2 Determination Test. The results showed: 1) The audit committee had no effect on firm value 2) Managerial ownership had a significant positive effect on firm value 3) Board of Commissioners had a significant positive effect on firm value 4) CSR had no effect on firm value.Keywords: Audit Committee, Managerial Ownership, Board of Commissioners, CSR, Company Value